Fixed Point Theorems for a Demicontractive Mapping and Equilibrium Problems in Hilbert Spaces - Khuangsatung, Wongvisarut; Suwannaut, Sarawut (Communications in Mathematics and Applications, 2020)
In this research, we introduce some properties of demicontractive mapping and the combination of equilibrium problem. Then, we prove a strong convergence for the iterative sequence converging to a common element of fixed point set of demicontractive mapping and a common solution of equilibrium problems. Finally, we give a numerical example for the main theorem to support our results.